Water content in diet affects growth and timing of female first mating, but not coloration, in the admirable grasshopper (Syrbula admirabilis). Issue 4 (5th December 2021) - de la Hera, Iván; Reichert, Michael S.
Abstract: Understanding how water limitation affects the performance of herbivorous insects is relevant in a context of worldwide alterations of rainfall regimes due to climate change. Apart from its influence on insect growth and development, water availability has also been considered a cue for color polyphenism in some species. This is the case of the grassland‐inhabiting admirable grasshopper ( Syrbula admirabilis ), for which water content in plant tissues, a potentially reliable cue to predict future vegetation conditions, has been proposed to determine the frequency of green–brown color morphs. We performed an experiment that manipulated water content of the diet (dry/wet treatment) in a group of individually monitored admirable grasshoppers to explore the effects on imago size, timing of female first mating, and coloration. Our results showed that grasshoppers in the wet treatment achieved larger sizes, and females mated comparatively earlier, than their counterparts in the dry treatment. We also found that hue (the dominant color) in imagines was significantly lower (browner) than in nymphs, but the magnitude of this color shift did not differ between treatments. This study supports the idea that water limitation has a negative impact on grasshopper growth and development, but rules out dietary water content as a cue for color polyphenism. This result encourages additional research to assess the actual contribution of environmental and genetic factors to color determination in admirable grasshoppers. Such information could help to better understand how color polymorphism is maintained in natural populations and to predict how it could evolve in a future in which environmental conditions will become more unpredictable.